Australian beef industry worker's knowledge, attitudes and practices regarding Q fever: A pilot study. Issue 43 (8th October 2019) - Wiley, Kerrie E.; Walker, Jacina; Lower, Tony; Massey, Peter D.; Durrheim, David N.; Khandaker, Gulam
Abstract: Background: Q fever is a vaccine-preventable zoonotic infection with potentially severe health outcomes and high economic costs that affects agricultural workers, including beef and cattle industry workers, however this population historically have sub-optimal vaccine uptake. Objective: To gather quantitative and qualitative pilot data from Australian beef industry workers on their knowledge, attitudes and practices around Q fever and Q fever vaccination. Methods: A mixed methods approach was used to ascertain the Q fever disease risk perception and vaccination behavior of a purposive convenience sample of beef industry workers attending an industry expo in Rockhampton, Queensland, Australia between May 7th and 9th, 2018. Results: The quantitative survey response rate was 83% (n = 86). More than 70% of respondents reported exposure to known Q fever risk factors. Eighty six percent were aware of Q fever, the self-reported uptake of Q fever vaccine was 27% and 9% reported undertaking testing which showed evidence of previous infection. Five main themes emerged from the qualitative data: "Finding the time" among other life priorities to attend a doctor for a vaccine; "Employer responsibility" to provide the vaccine; "My doctor knows me" and could suggest Q fever vaccination; "Assigning Risk" across a range of attitudes, including thinking it would not happen to them, 'fatalism', and knowing the danger but taking the risk anyway; and "The Need for Outreach" vaccine delivery services in their communities. Significance: These data suggest that a coordinated public health approach to testing and vaccine provision, coupled with an awareness campaign among regional doctors to prompt them to routinely ask patients about their Q fever risk and vaccination history, should form part of a broad approach to Q fever control and prevention.